2019
DOI: 10.1021/acs.jpclett.9b01264
|View full text |Cite
|
Sign up to set email alerts
|

Discerning Bulk and Interfacial Polarons in a Dual Electron Donor/Acceptor Polymer

Abstract: The active layer of organic solar cells typically possesses a complex morphology, with amorphous donor/acceptor mixed domains present in addition to purer, more crystalline domains. These crystalline domains may represent an energy sink for free charges that aids charge separation and suppresses bimolecular recombination. The first step in exploiting this behavior is the identification and characterization of charges located in these different domains. Herein, the generation and recombination of both bulk and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…Oxygen quenching experiments are standard procedures in µs-TAS and have been applied successfully to many conjugated polymer systems. [5,74,85] The short oxygen exposure times in such experiments usually preclude oxygen-induced degradation. The key to successful use of our TCA methodology is therefore an assessment of the reversibility of the reaction (Figure S7, Supporting Information): any oxygen-induced degradation will prevent a full reversibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Oxygen quenching experiments are standard procedures in µs-TAS and have been applied successfully to many conjugated polymer systems. [5,74,85] The short oxygen exposure times in such experiments usually preclude oxygen-induced degradation. The key to successful use of our TCA methodology is therefore an assessment of the reversibility of the reaction (Figure S7, Supporting Information): any oxygen-induced degradation will prevent a full reversibility.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that certain materials have the ability to form polarons in both crystalline and amorphous regions, showing two different polaron absorbance features. [74,75] For this particular approach, the energy sink phenomenon may play an important role: polarons, once formed, may be rapidly transferred to more crystalline domains. [92,93]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is highly unusual because conjugated polymers in solution often display only triplet formation, 32 and for those that are capable of charge generation in solution or pristine films, these charges generally decay on nanosecond timescales due to rapid geminate recombination. 9 The charge generation process in the pristine polymer solution is likely aided by the strongly intramolecular donor/acceptor nature of PCPDT-sFCN , providing significant charge-transfer character to the lowest energy singlet state. The spatial separation of electron and hole in this CT state reduces the exciton binding energy, and this, coupled to the aggregate configuration with multiple interchain interactions, allows the separated charges to form (depicted in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, any charges that do form tend to undergo rapid geminate recombination on ps-ns timescales. 8,9 Furthermore, many pristine conjugated polymers exhibit solely triplet formation. 10,11 Triplet states are a key species that commonly form during the operation of organic electronic devices such as light emitting diodes and solar cells.…”
Section: Introductionmentioning
confidence: 99%